Calculation of the inundation of 1746 tsunami of Callao - Jimenez, Cesar (2023)
On October 28, 1746, at 22:30 local time, the city of Lima and Callao were shaken by a strong earthquake of magnitude Mw 8.6 and intensity X e¿in the Mercalli scale, the epicenter was located in the sea offshore Callao. The tsunami destroyed the city of Callao and produced the death of more than 5000 people, remaining only 200 survivors. From historical catalogue the seismic parameter of the earthquake are obtained, then the rupture parameters are calculated. With the help of WinITDB model the maximum tsunami wave height is calculated. From the wave equation fro shallow water and with the bathymetry data the arrival times of the leading wave are calculated. For calculating the run-up or maximum inundation height, a dynamic and energetic model of one particle is used. This will allow the elaboration of an inundation map, which will be usefulmess for mitigation of the disaster on the part of the corresponding authorities.